2008
DOI: 10.1111/j.1365-2559.2008.03101.x
|View full text |Cite
|
Sign up to set email alerts
|

Is sclerosing angiomatoid nodular transformation (SANT) of the splenic red pulp identical to inflammatory pseudotumour? Report of 16 cases

Abstract: SANT of the red pulp is a distinct benign pseudotumorous lesion of the spleen characterized by the presence of angiomatoid nodules. We observed such angiomatoid nodules in all our cases of splenic IPT, which were not follicular dendritic cell or myofibroblastic tumours. We therefore recommend careful examination for angiomatoid nodules in all suspected cases of splenic IPT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
53
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 8 publications
5
53
0
2
Order By: Relevance
“…This suggests the possibility of a secondary response possibly to vascular obstruction and/or intratumoral thrombosis. In fact, sclerosing angiomatoid nodular transformation-like features can be commonly seen in the presence of thrombosed vessels, occurring both in reactive (eg thrombosed hemorrhoids) as well as neoplastic settings (eg surrounding metastases), as also suggested by Diebold et al 38 Sclerosing angiomatoid nodular transformation-like lesions have been described in spleens involved by carcinomas 39 and in the presence of splenic extramedullary hematopoiesis, particularly in cases with large extramedullary hematopoiesis nodules associated with sclerosis, a lesion also known as sclerosing extramedullary hematopoietic tumor. 40 In a proportion of these cases, the presence of fibrotic stroma containing CD34-positive capillaries, but devoid of CD8-positive sinuses, result in a distinct nodularity and a close resemblance to sclerosing angiomatoid nodular transformation (Orazi, unpublished observation).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This suggests the possibility of a secondary response possibly to vascular obstruction and/or intratumoral thrombosis. In fact, sclerosing angiomatoid nodular transformation-like features can be commonly seen in the presence of thrombosed vessels, occurring both in reactive (eg thrombosed hemorrhoids) as well as neoplastic settings (eg surrounding metastases), as also suggested by Diebold et al 38 Sclerosing angiomatoid nodular transformation-like lesions have been described in spleens involved by carcinomas 39 and in the presence of splenic extramedullary hematopoiesis, particularly in cases with large extramedullary hematopoiesis nodules associated with sclerosis, a lesion also known as sclerosing extramedullary hematopoietic tumor. 40 In a proportion of these cases, the presence of fibrotic stroma containing CD34-positive capillaries, but devoid of CD8-positive sinuses, result in a distinct nodularity and a close resemblance to sclerosing angiomatoid nodular transformation (Orazi, unpublished observation).…”
Section: Discussionmentioning
confidence: 59%
“…Similar lesions have been described by others. 36,37 In a more recent series of sclerosing angiomatoid nodular transformation cases, published by Diebold et al, 38 one of the lesions was found adjacent to a splenic hemangioma. This suggests the possibility of a secondary response possibly to vascular obstruction and/or intratumoral thrombosis.…”
Section: Discussionmentioning
confidence: 98%
“…EBV (in situ hybridization for EBER) has been found in spleen and liver IPT in higher frequency than in lymph node (66%, 50% and 20%, respectively [20,38,[47][48][49][50]. Tuberculosis should be included in differential diagnosis [51], as well as sclerosing angiomatoid transformation of the spleen [52][53][54].…”
Section: Inflammatory Pseudotumor In Lymph Nodes and Spleenmentioning
confidence: 99%
“…Microscopically, the nodules show a variable admixture and sieve like arrangement of vascular spaces that represent an admixture of cells lining splenic sinusoids, capillaries and veins (4). The degree of circumscription of nodules by collagen and the quality of the intervening stroma (whether fibromyxoid, sclerotic or hyaline) may vary negative for CD34 unlike the mixed immune-expression of SaNT.…”
Section: Discussionmentioning
confidence: 99%